2020
DOI: 10.1182/bloodadvances.2020002346
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the narrow bridge to CAR T-cell therapy

Abstract: When the pivotal phase 2 ZUMA-1 trial was first published in the New England Journal of Medicine in 2017, chimeric antigen receptor (CAR) T-cell therapy was widely regarded as a major breakthrough for patients with refractory diffuse large B-cell lymphoma. These patients, who historically would have had dismal outcomes, had an objective response rate of 82% and an 18-month overall survival of 52%. 1 The results of ZUMA-1 were subsequently bolstered by the JULIET study, in which patients had an equally impressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Finally, in a phase 2 DLBCL study, BRT patients had higher overall response rate, less severe CRS, and less neurotoxicity compared to chemotherapy‐bridged patients 19 . These results and others suggest that priming with RT may be more effective than chemotherapy 20,21 . Our case differed from those reported in the above series in that our patient was in a clinically precarious situation, and the RT dose given (12 Gy) was selected to produce a local response as a bridge to CAR‐T, but also with the goal of avoiding significant late cardiac toxicity that may have occurred with a more definitive RT dose of 24‐30 Gy.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…Finally, in a phase 2 DLBCL study, BRT patients had higher overall response rate, less severe CRS, and less neurotoxicity compared to chemotherapy‐bridged patients 19 . These results and others suggest that priming with RT may be more effective than chemotherapy 20,21 . Our case differed from those reported in the above series in that our patient was in a clinically precarious situation, and the RT dose given (12 Gy) was selected to produce a local response as a bridge to CAR‐T, but also with the goal of avoiding significant late cardiac toxicity that may have occurred with a more definitive RT dose of 24‐30 Gy.…”
Section: Resultsmentioning
confidence: 57%
“…19 These results and others suggest that priming with RT may be more effective than chemotherapy. 20,21 Our case differed from those reported in the above series in that our patient was in a clinically precarious situation, and the RT dose given (12 Gy) was selected to produce a local response as a bridge to CAR-T, but also with the goal of avoiding significant late cardiac toxicity that may have occurred with a more definitive RT dose of 24-30 Gy. An earlier report showed that there may be a disease control advantage to irradiating all sites of disease prior to CAR-T as compared to only a subset of sites, though it remains unclear whether the potential toxicity of doing so could outweigh this benefit.…”
Section: Debulking and Brtmentioning
confidence: 83%
See 2 more Smart Citations
“…There is a wide spectrum of bridging therapy options in the literature. 31 Radiotherapy as a bridging treatment in CAR T-cell therapy is being researched 32 and one such patient with DLBL had a partial response and no adverse events due to radiotherapy were observed in the two patients in this study.…”
Section: Discussionmentioning
confidence: 81%